Bilateral spontaneous pneumothorax in systemic lupus erythematosus and the role of low-dose intravenous immunoglobulin - Liauw, Felix; Paramita, Tiara Nien; Citraresmi, Endah; Hadi, Abdurrahman (Journal of yeungnam medical science, 2025)
KCI Citation Count: 0